HPLC-UV Determination of Abacavir Sulphate in Pharmaceutical Dosage Forms - SHANTA KUMARI, A.; PRAKASH, K.; NAGOJI, K.E.V.; RAO, M.E.B. (Asian Journal of Chemistry, 2010)
A new reverse phase high performance liquid chromatographic (RPHPLC) method with UV detection was developed and used for the estimation of abacavir sulphate (ABS) in bulk and pharmaceutical dosage forms using RPC-18 column using an isocratic HPLC system. The mobile phase consisted of acetonitrile and 0.05 M potassium dihydrogen phosphate (pH 4.2) in the ratio of 50 : 50 at a flow rate of 1 mL/min. The run time was 15 min. Nelfinavir mesylate (NEM) (50 μg/mL) was used as an internal standard. The detection was carried out at 220 nm and the linearity was found to be in the range of 0.5-200 μg/mL. The retention times for drug (ABS) and internal standard (NEM) were 3.558 and 10.725 min, respectively. Recovery studies showed that ca. 99.87 % of ABS could be recovered from the preanalyzed samples indicating high accuracy of proposed method. There was no intra-day and inter-day variation found in the method of analysis. The mean drug content in branded ABS tablet dosage forms was quantified and found to be between 99.64 and 100.05%. The method was found to be simple, precise, specific, sensitive and reproducible.